ICU Mortality Prediction Using XGBoost-based Scoring Systems: A Study from a Developing Country - Karasneh, Reema; Al-Azzam, Sayer; Alzoubi, Karem H.; Araydah, Mohammad; Rahhal, Dania; Al-Azzam, Yamin; Kharaba, Zelal; Kabbaha, Suad; Aldeyab, Mamoon A (Reviews on Recent Clinical Trials, 2025)
<span class=
Keywords: cohort study